The synaptic interplay of Tau and Aβ oligomeric species in Alzheimer's disease and related tauopathies. (20th December 2022) - Marcatti, Michela; Fracassi, Anna; Montalbano, Mauro; Puangmalai, Nicha; Bhatt, Nemil; Natarajan, Chandramouli; Guptarak, Jutatip; Krishnan, Balaji; Kayed, Rakez; Taglialatela, Giulio
Abstract: Background: Alzheimer's Disease (AD) is characterized by gradual cognitive decline driven by the targeting of synapses by small oligomers of both Aβ (AβO) and tau (TauO), which results in synaptic dysfunction that ultimately underscores disease progression. Preventing the interaction of these oligomers with synapses might be effective to treat AD. However, clinical trial failures suggest low effectiveness of targeting Aβ in late‐stage AD thus redirecting the attention onto TauO whose levels increase later in the disease timeline. Here we show that TauO and AβO target synapses with different dynamics. Method: We used recombinant AbO and TauO as well as human brain derived tau oligomers from AD (BDTO‐AD), and from Progressive Supranuclear Palsy (BDTO‐PSP). Analyses of flow‐cytometry, western blot, immunofluorescence, and proteinase K digestion were performed to study the binding dynamic of the oligomers onto synaptosomes isolated from human frontal cortex and hippocampus. AβO and TauO were injected ICV in 3xTgAD, Tg2576 and h‐Tau mice for our in vivo experiments. The synaptic dysfunction was measured by FASS‐LTP assay. Result: We found that recombinant TauO, BDTO‐AD and BDTO‐PSP oucompete AβO and become the prevailing synaptic‐associated species, while high concentrations of AβO facilitate the recruitment of tau oligomers at the synapses. Immunofluorescence analyses of mouse primary cortical neurons treated with AβO and/or TauO as well as in vivo experiments using 3xTgAD, Tg2576 and h‐Tau mice injected ICV with AβO or TauO supported these findings. Consistent with these observations, FASS‐LTP analyses demonstrated that TauO‐induced suppression of chemical LTP was exacerbated by AβO. Moreover, depletion of synaptosome surface proteins by PK pre‐treatment abolished the effect of TauO in reducing AβO synaptic binding without affecting the ability of high AbO levels to increase synaptic TauO recruitment. Furthermore, we observed different synaptic engagement and internalization profiles among the analyzed BDTOs. Conclusion: Overall, our results suggest that, as the disease progresses, TauO outcompete AβO at the synapses, thus becoming the driver of the synaptic dysfunction responsible for the cognitive decline at the late stage of AD. Furthermore, disease‐specific differences in the dynamic of BDTOs engagement of synapses may indicate different synaptic toxicity of TauO across the tauopathies spectrum.